Pengentasan buta aksara berbasis pendekatan â€œsemua anak cerdasâ€ untuk guru SD - Rosyidah, Awal Nur Kholifatur; Affandi, Lalu Hamdian; Erfan, Muhammad; Oktaviyanti, Itsna; Maulyda, Mohammad Archi; Hamdani, Iwan (University of Islam Malang, 2021)
This service activity aims to improve the literacy and numeracy skills of elementary school (SD) children in Karang Sidemen Village, North Batukliang District, Central Lombok Regency through the